Longitudinal assessment of immunogenicity of inactivated COVID-19 booster immunization and breakthrough infection in blood donors: A multicenter study from 2021 to 2023 - Ying Yan; Shana Halemubieke; Baifeng Shan; Lei Zhao; Youbin Duan; Yifang Wang; Mingrui Wu; Xiaoxiao Bu; Quaner Wang; Le Chang; Huimin Ji; Huizhen Sun; et al. (Human Vaccines & Immunotherapeutics)
Assessing immune responses across diverse populations is essential for refining public health strategies. Blood donors offer valuable insights into community-level immunity. This study aims to investigate immune responses associated with inactivated COVID-19 booster immunization and breakthrough infections in blood donors. This study was conducted in a cohort of blood donors from six centers across five of China’s seven major geographical regions, spanning from December 2021 to February 2023. Blood samples were collected before booster vaccination, at 1, 3, and 6 months post-vaccination, as well as 1 month post-infection. SARS-CoV-2-specific antibodies, T cell specific IFNγ levels, and neutralizing antibodies against wild-type and Omicron strains were measured. Platelet count, anti-PF4 antibody, and D-dimer levels were assessed. Demographic characteristics were analyzed to determine their impact on immunogenicity. SARS-CoV-2-specific antibodies and IFNγ levels significantly increased post-booster, peaking one month after immunization. Antibodies continued to decrease at six months, while IFNγ levels remained stable at this point. Pseudovirus neutralization assays revealed elevated neutralizing antibodies following the booster dose, with minimal response to the XBB.1.5 variant. Following Omicron infection, antibody and IFNγ levels surpassed that observed post-booster. Participants aged 36–49 and those over 50 exhibited weaker immune responses post-booster than those ages 18–35, while those with BMI above 28 showed lower IFNγ levels. This study demonstrates the utility of blood donor samples for tracking immunization effectiveness against emerging pathogens, and highlights enhanced immune responses after booster immunization and breakthrough infections, underscoring the need for tailored vaccination strategies for different groups.